The Issues Related to Studying of Language and thought in Cognitive Linguistics - Ibragimjonovna, Ahmedova Matlubaxon; qizi, Tuxtanazarova Sarvinoz Umidjon (Miasto Przyszłości, 2023)
In this article, various opinions and considerations about whether language is a social or natural phenomenon are considered, and it is emphasized that it is a social phenomenon. At the same time, the issues of the relationship between language and thought and its study in cognitive linguistics are considered.